Chemotherapy after immune checkpoint blockade in patients with recurrent, metastatic squamous cell carcinoma of the head and neck. (June 2020) - Kacew, Alec J.; Harris, Ethan J.; Lorch, Jochen H.; Schoenfeld, Jonathan D.; Margalit, Danielle N.; Kass, Jason I.; Tishler, Roy B.; Haddad, Robert I.; Hanna, Glenn J.
Highlights: 5-FU- and platinum-based regimens may be superior in the post-immunotherapy setting. Doublet and triplet regimens appear to be superior following immunotherapy failure. Platinum and immunotherapy re-challenge may be reasonable options. Abstract: Objectives: Given that immune checkpoint inhibitors (ICIs) are now preferred agents in first-line treatment of recurrent/metastatic (R/M) squamous cell carcinoma of the head and neck (SCCHN), we retrospectively studied outcomes on post-ICI therapies. Materials and methods: We collected data from the medical records of 60 patients with R/M SCCHN who received ICIs followed by at least one further line of cytotoxic or biologic therapy at our institution from 2014 to 2019. We also compared outcomes with those of historical trials in the ICI-naïve, second-line or greater setting. Results: Patients who received platinum-based regimens as their post-ICI therapies experienced improved overall response (ORR) (50% versus 10%, p < 0.01) and improved overall survival (OS) (15.1 months versus 7.3 months, HR 0.46, p = 0.04) compared to the rest of the cohort. Patients receiving platinum re-challenge were more likely to respond than all other patients in the cohort (OR 8.37, p = 0.01). The ORR for patients on 5-fluorouracil (5-FU)-containing regimens (63%) was also higher than other patients in the cohort (p = 0.03). Immunotherapy-based regimens compared favorably to historical data of first exposure to ICIs (disease control rate 54% versus 36%). Singlet regimens were associated with shorter OS than other regimens (HR = 2.38, p = 0.01). Conclusions: Platinum- and 5-FU-based doublet or triplet regimens may be superior options in the post-ICI setting. Immunotherapy re-challenge following ICI therapy may also be a reasonable option.